Juvenile Social Isolation Enhances the Activity of Inhibitory Neuronal Circuits in the Medial Prefrontal Cortex - Yamamuro, Kazuhiko; Yoshino, Hiroki; Ogawa, Yoichi; Okamura, Kazuya; Nishihata, Yosuke; Makinodan, Manabu; Saito, Yasuhiko; Kishimoto, Toshifumi (Frontiers in Cellular Neuroscience, 2020)
During brain development, the design of primary neural networks is primarily determined by environmental stimuli after their formation. In particular, the juvenile period is critical, during which neuronal circuits that consist of both excitatory and inhibitory neurons are remodeled by experience. Social isolation during the juvenile period profoundly affects brain development and contributes to the development of psychiatric disorders. We previously reported that 2 weeks of social isolation after weaning reduced excitatory synaptic inputs and intrinsic excitability in a subtype of layer 5 pyramidal cells, which we defined as prominent h-current (PH) cells, in the medial prefrontal cortex (mPFC) in mice. However, it remains unclear how juvenile social isolation affects inhibitory neuronal circuits that consist of pyramidal cells and interneurons. We found that 2 weeks of social isolation after weaning increased inhibitory synaptic inputs exclusively onto PH cells with a concomitant deterioration of action potential properties. Although social isolation did not alter the inhibitory synaptic release mechanisms or the number of inhibitory functional synapses on PH cells, we found that it increased the intrinsic excitability of fast-spiking (FS) interneurons with less excitatory synaptic inputs and more h-current. Our findings indicate that juvenile social isolation enhances the activity of inhibitory neuronal circuits in the mPFC.